The impact of political violence on posttraumatic stress symptomology: a longitudinal analysis. Issue 2 (4th March 2022) - Saltzman, Leia Y.; Canetti, Daphna; Hobfoll, Stevan E.; Hall, Brian J.
ABSTRACT: Objective: The current paper uses the Conservation of Resources Theory to frame an examination of the impact of exposure to political violence on posttraumatic stress symptomology among three groups within Israeli society: (1) Native Born Jews; (2) Foreign Born Jews; and (3) Palestinian Citizens of Israel. Methods: The study population was a large nationally representative sample of 1613 respondents collected during The Second Intifada. The sample consists of approximately 40% Jews born in Israel ( n = 652), 30% ( n = 484) were Jews who immigrated to Israel, and close to 30% ( n = 477) were Palestinian Citizens of Israel. Mediation analyses explored the role of resource loss in the relationship between social status and posttraumatic stress disorder (PTSD) symptom severity. Results: Compared to native born Jews, foreign born Jews and Palestinian Citizens of Israel reported greater PTSD symptom severity at wave III. These relationships were not mediated by psychosocial resource loss or economic resource loss. Conclusions: We discuss the importance of tailored interventions with minority groups in the context of ongoing political violence.